Government Spending and Legislative Organization: Quasi-experimental evidence from Germany - Peter Egger; Marko Koethenbuerger (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
This paper presents empirical evidence of a positive effect of council size on government spending using a data set of 2,056 municipalities in the German state of Bavaria over a period of 21 years. We apply a regression discontinuity design to avoid an endogeneity bias. In particular, we exploit discontinuities in the legal rule that relates population size of a municipality to council size to identify a causal relationship between council size and public spending, and find a robust positive impact of council size on spending. Moreover, we show that municipalities primarily adjust current expenditure in response to a rise in council size.
Keywords: D7; H7; C2; 330; Legislative organization; Regression-discontinuity design; Government spending; Mayor-council system; Öffentliche Ausgaben; Gesetzgebung; Neue politische Ökonomie; Regression; Kommunalverwaltung; Bayern; Deutschland